RNA-Seq Analysis Reveals the Role of Omp16 in Brucella-Infected RAW264.7 Cells - Zhou, Dong; Zhi, Feijie; Fang, Jiaoyang; Zheng, Weifang; Li, Junmei; Zhang, Guangdong; Chen, Lei; Jin, Yaping; Wang, Aihua (Frontiers in Veterinary Science, 2021)
Brucellosis is an endemic zoonotic infectious disease in the majority of developing countries, which causes huge economic losses. As immunogenic and protective antigens at the surface of Brucella spp., outer membrane proteins (Omps) are particularly attractive for developing vaccine and could have more relevant role in host–pathogen interactions. Omp16, a homolog to peptidoglycan-associated lipoproteins (Pals), is essential for Brucella survival in vitro. At present, the functions of Omp16 have been poorly studied. Here, the gene expression profile of RAW264.7 cells infected with Brucella suis vaccine strain 2 (B. suis S2) and ΔOmp16 was analyzed by RNA-seq to investigate the cellular response immediately after Brucella entry. The RNA-sequence analysis revealed that a total of 303 genes were significantly regulated by B. suis S2 24 h post-infection. Of these, 273 differentially expressed genes (DEGs) were upregulated, and 30 DEGs were downregulated. These DEGs were mainly involved in innate immune signaling pathways, including pattern recognition receptors (PRRs), proinflammatory cytokines, and chemokines by Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. In ΔOmp16-infected cells, the expression of 52 total cells genes was significantly upregulated and that of 9 total cells genes were downregulated compared to B. suis S2-infected RAW264.7 cells. The KEGG pathway analysis showed that several upregulated genes were proinflammatory cytokines and chemokines, such as interleukin (IL)-6, IL-11, IL-12β, C–C motif chemokine (CCL2), and CCL22. All together, we clearly demonstrate that ΔOmp16 can alter macrophage immune-related pathways to increase proinflammatory cytokines and chemokines, which provide insights into illuminating the Brucella pathogenic strategies.